2000
DOI: 10.3758/bf03211839
|View full text |Cite
|
Sign up to set email alerts
|

Attribute centrality and imaginative thought

Abstract: Participants' representations of the concept human were examined to differentiate three types of associations between concepts and their component attributes: the capacity of concepts to cue attributes (attribute accessibility), the capacity of attributes to cue concepts (instance accessibility), and the extent to which attributes are thought of as central to concepts (attribute centrality), The findings provide information about the concept human itself and, more generally, about the functionally distinct rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The underlying theory suggests that when facing a problem, the default approach of people is to implement the first solution that comes to mind (Ward, 1994). The first solution coming to mind is typically based on analogies to a previous solution and therefore fits comfortably with the new problem (Ward, 1994;Ward and Dodds, 2000).…”
Section: Financial Resource Constraints As Enablers Of Innovationmentioning
confidence: 99%
“…The underlying theory suggests that when facing a problem, the default approach of people is to implement the first solution that comes to mind (Ward, 1994). The first solution coming to mind is typically based on analogies to a previous solution and therefore fits comfortably with the new problem (Ward, 1994;Ward and Dodds, 2000).…”
Section: Financial Resource Constraints As Enablers Of Innovationmentioning
confidence: 99%
“…Similar to the findings of Scott, Lonergan, and Mumford (2005), which stated that conceptual combination in creative thought might proceed using alternative approaches (analogical or case-based approach) according to the nature of the knowledge being applied, the present study demonstrates the strategies used in creative idea generation might be regulated by domain knowledge. However, such results would not refute the path-of-least-resistance model (Ward, 1994;Ward, 1995;Ward, Dodds, Saunders, & Sifonis, 2000), which suggests that people's predominant tendency, when they develop new ideas in a domain, is to retrieve fairly specific, basic level exemplars from that domain as a beginning point. Once again, the present study confirms this notion.…”
Section: Discussionmentioning
confidence: 79%
“…Following the research line mentioned above, the present study investigated the role of domain knowledge in creative idea generation. Previous studies revealed that when people generate new ideas for a domain, their predominant tendencies are to retrieve fairly specific, basic level exemplars from that domain, select one or more of those instances as a starting point, and project many of the stored properties of the instances into the novel ideas (Ward, 1994;Ward, 1995;Ward, Dodds, Saunders, & Sifonis, 2000). Meanwhile, a minority of people tested depend on more abstract information (e.g., features of category membership) and generate more original ideas than those relying on specific instances (Ward, Patterson, Sifonis, Dodds, & Saunders, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The path-of-least-resistance model suggests that new ideas are developed starting from the basic instances for the problem context, and projecting their features to the new solutions (Ward, 1995;Ward et al, 2000).…”
Section: Aggregating Elements Divergent Elements and Universal Connmentioning
confidence: 99%